Least restrictive practices: an evaluation of patient experiences - Hui, Ada (University of Nottingham, 2017)
The uses of restrictive practices have become increasingly controversial over recent decades. With an increasing emphasis in recovery orientated values and person centred care, the uses of restrictive practices have become ever more contentious. National and international policies and guidelines have called for a reduction in the uses of these practices and interventions, and emphases on ‘least restrictive practices’ have been outlined. The notion of ‘least restrictive practices’ however, is not clearly defined. Limited research has been conducted to examine the uses of restrictive practices specifically within forensic mental health services. Little is known with regards how patients perceive and experience restrictive practices within high security hospital settings. It is therefore timely to consider patient experiences of restrictive practices and interventions, specifically within the context of a forensic high security mental health hospital. This study aims to explore patients’ experiences of restrictive practices and interventions within Rampton High Security Hospital.